New findings of the family Pardaliscidae from the deep-sea southwestern Atlantic: the genus Caleidoscopsis Karaman, 1974 - Nascimento, Priscila S. Do; Serejo, Cristiana S. (Zootaxa, 2023)
Caleidoscopsis is a deep-sea pardaliscid genus known previously only from the SE Atlantic Ocean (Angola Basin), NE Pacific Ocean (Mexico, Cedros Trench) and Indian Ocean (Madagascar). This is the first record of Caleidoscopsis from off the Brazilian coast, SW Atlantic Ocean. Samples were collected with box core and/or van veen grabs between Espírito Santo, Campos and Santos Basin (19o–27o S), and around 417–1974 m depths. Two new species is herein described, Caleidoscopsis carlosi sp. nov., which differs from all Caleidoscopsis species by antenna 1 geniculate; maxilliped palp, article 4 shorter than 3; pereopods 5–7, propodus shorter than dactylus; and pereopod 7 with propodus 7x longer than wide; and Caleidoscopsis karamani sp. nov., which can be distinguished by rostrum more developed, reaching half-length of article 1 of peduncle of antenna 1; antenna 2, peduncle, article 5 longer than 3 and 4; pereopod 7, propodus 13x longer than wide, subequal to dactylus; urosomite 1 covering part of urosomite 2, with 1 long dorsal tooth; urosomite 2 with 1 very long and thin dorsal tooth almost reaching the end of urosomite 3. Further on, Caleidoscopsis carlosi sp. nov. turn out to be a very common and abundant species along the study area, being found in 126 samples with a total of 146 specimens examined, when comparing with C. karamani sp. nov. that was found in only 5 samples with one individual each. A table of comparison and an identification key of the currently six known species of the genus are provided. The present study is an effort in understanding and unrevealing the deep-sea macrofauna from the Brazilian margin bringing new data on the family Pardaliscidae found in the slope of the Campos, Santos and Espírito Santo Basins.